Good Faith and Law Evasion - Buell, Samuel W. (2011)
Laws imposing sanctions can be self-defeating by supplying incentive and guidance for actors engaged in socially undesirable activities to reshape conduct to avoid penalties. Sometimes this is deterrence. But if the new activity, as much as the old, contravenes the normative stance of the legal project, it is a failure of law. The problem of evasion warrants response in many fields - not least in criminal law despite the frequent and too simple assumption that legality-related values require narrow prohibitions that unavoidably permit evasion. Three common responses to evasion have serious deficits. Foregoing control of evasion is a mistake if large portions of an activity warranting regulation occur along (and move towards) the margins of a legal rule. Regulating through frequent iteration of narrow rules is costly and may leave law a step behind moving targets. Using broad standards inevitably leads to overbreadth, creating space for mischief in the form of excess enforcement discretion and sanctioning of undeserving persons. A fourth approach holds more promise and has escaped treatment in scholarship. Law can proceed more directly by using doctrine designed to identify the evasive actor. I argue that mental state inquiry is the best way to do this; demonstrate that the law has long engaged in a version of this approach in its use of some good faith doctrines; and conclude that this form of good faith doctrine could be further exploited to respond to evasion problems in criminal and corporate law